Profil Usaha Peternak Sapi Di Desa Jogoresan Kecamatan Purwodadi Kabupaten Purworejo : Business Profile of Cattle Farmers In Jogoresan Village, Purwodadi District, Purworejo Regency - Ariana, Ela Rosita; Zulfanita, Zulfanita; Iskandar, Faruq (Jurnal Riset Agribisnis dan Peternakan, 2024)
This study aims to determine the business profile and characteristics of cattle farmers in Jogoresan Village, Purwodadi Subdistrict. The population of this study were 142 cattle farmers. Sampling used the Slovin formula calculation with an error rate of 10% so that the sample size was 60 farmers. Data collection instruments used questionnaires and interviews. The results of data analysis show that the process of cattle farming run by Jogoresan Village farmers is still carried out traditionally so that public awareness of livestock programs provided by the government is still low. The busyness of farmers also affects the concentration of farmers in running their business because the livestock business is not the main job.